161k views
3 votes
(5j − 2q) − (− 4 + 3j − 6q) PLEASE I WILL GIVE YOU 15 POINTS

2 Answers

3 votes

Answer:

which difference between us two is the only way that I know what I am going through and 7

Explanation:

r GG cftrfft4 I am going out of the following was the first and I thought

User Sanjayrajsinh
by
4.5k points
5 votes

Answer: 2j + 4q + 4

Distribute the Negative Sign:

=5j−2q+−1(−4+3j−6q)

=5j+−2q+(−1)(−4)+−1(3j)+−1(−6q)

=5j+−2q+4+−3j+6q

Combine Like Terms:

=5j+−2q+4+−3j+6q

=(5j+−3j)+(−2q+6q)+(4)

=2j+ 4q + 4

:D

User Anky
by
5.3k points